Ротаційні криві галактик у підході до темної матерії на основі µ-деформації - Gavrilik, A. M.; Kachurik, I. I.; Khelashvili, M. V. (Publishing house "Academperiodika", 2019)
We elaborate further the м-deformation-based approach to the modeling of dark matter, in addition to the earlier proposed use of м-deformed thermodynamics. Herein, we construct м-deformed analogs of the Lane–Emden equation (for density profiles) and find their solutions. Using these, we plot the rotation curves for a number of galaxies. Different curves describing the chosen galaxies are labeled by respective (different) values of the deformation parameter м. As a result, the use of м-deformation leads to the improved agreement with observational data. For all the considered galaxies, the obtained rotation curves (labeled by м) agree better with data, as compared to the well-known Bose–Einstein condensate model results of T. Harko. Besides, for five of the eight cases of galaxies, we find a better picture for rotation curves, than the corresponding Navarro–Frenk–White (NFW) curves. The possible physical meaning of the parameter м basic for this version of м-deformation is briefly discussed.